2017
DOI: 10.18203/2320-1770.ijrcog20171414
|View full text |Cite
|
Sign up to set email alerts
|

First trimester bleeding and pregnancy outcome

Abstract: Background: The outcome of first trimester vaginal bleeding is a matter of debate. This study sought to determine the maternal and perinatal outcome in patients presenting with first trimester vaginal bleeding.Methods: This prospective observational study was done on 1007 women with first trimester vaginal bleeding at a tertiary care hospital in Mumbai over a period of one year. A detailed history was taken and USG was done to confirm diagnosis. All these patients were evaluated for the outcomes including  thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Contradictory to our study, Kamble et al found that incidence of abortion was higher in patients with first trimester bleeding in less than 6 weeks of gestation (77%) whereas it was significantly less after 10 weeks of gestation (7%). 24 Among the total number of our cases we found higher prevalence of several risk factors which contributed for early pregnancy losses were hypothyroidism, substance abuse, obesity, history of recurrent abortion, patient conceived after infertility treatments and IVF. Sharma et al found a significant association of thyroid function with an abortion rate of 14.63% in their study group, i.e., pregnant women with hypothyroidism (and 4.96% in their control group).…”
Section: Discussionmentioning
confidence: 58%
“…Contradictory to our study, Kamble et al found that incidence of abortion was higher in patients with first trimester bleeding in less than 6 weeks of gestation (77%) whereas it was significantly less after 10 weeks of gestation (7%). 24 Among the total number of our cases we found higher prevalence of several risk factors which contributed for early pregnancy losses were hypothyroidism, substance abuse, obesity, history of recurrent abortion, patient conceived after infertility treatments and IVF. Sharma et al found a significant association of thyroid function with an abortion rate of 14.63% in their study group, i.e., pregnant women with hypothyroidism (and 4.96% in their control group).…”
Section: Discussionmentioning
confidence: 58%
“…This is in concordance with the study of Kamble PD et al, in which vaginal delivery was 68.7% and LSCS was 31.3%. 33 Similarly, in study conducted by Patel NG et al, vaginal delivery was 59.5% and LSCS was 40.5% and most common indication of LSCS was fetal distress (60%). 18 In study conducted by Sarmalkar MS et al, rate of LSCS was 38% and most common indication was fetal distress (17%).…”
Section: Mode Of Deliverymentioning
confidence: 89%
“…A study by Manonmani and Nandini on 150 pregnant women with found that the majority cases with first trimester vaginal bleeding were in between 26-30 years (42%) [8] . A study by Kamble PD et al, found that the majority cases with first trimester vaginal bleeding were in between 21-30 years [6] . While Amirkhani et al, found 53% of cases in the age group between 25-34 years [9] .…”
Section: Discussionmentioning
confidence: 99%
“…First trimester bleeding is a threatening sign of abortion and is always associated with miscarriage and pregnancy complications [6] . Around 25% of pregnant women complain of bleeding during the first trimester [7] .…”
Section: Discussionmentioning
confidence: 99%